Acetylsalicylic Acid Prevents Intermittent Hypoxia-Induced Vascular Remodeling in a Murine Model of Sleep Apnea - Suarez-Giron, Monique C.; Castro-Grattoni, Anabel; Torres, Marta; Farré, Ramon; Barbé, Ferran; Sánchez-de-la-Torre, Manuel; Gozal, David; Picado, Cesar; Montserrat, Josep M.; Almendros, Isaac (Frontiers in Physiology, 2018)
Study objectives: Chronic intermittent hypoxia (CIH), a hallmark feature of obstructive sleep apnea (OSA), induces accelerated atherogenesis as well as aorta vascular remodeling. Although the cyclooxygenase (COX) pathway has been proposed to contribute to the cardiovascular consequences of OSA, the potential benefits of a widely employed COX-inhibitor such (acetylsalicylic acid, ASA) on CIH-induced vascular pathology are unknown. Therefore, we hypothesized that a common non-selective COX inhibitor such as ASA would attenuate the aortic remodeling induced by CIH in mice. Methods: 40 wild-type C57/BL6 male mice were randomly allocated to CIH or normoxic exposures (N) and treated with daily doses of ASA or placebo for 6 weeks. At the end of the experiments, intima-media thickness (IMT), elastin disorganization (ED), elastin fragmentation (EF), length between fragmented fiber endpoints (LFF), aortic wall collagen abundance (AC) and mucoid deposition (MD) were assessed. Results: Compared to N, CIH promoted significant increases in IMT (52.58±2.82 µm vs. 46.07±4.18 µm, p<0.001), ED (25.29±14.60 % vs. 4.74±5.37 %, p<0.001), EF (5.80±2.040.65 vs. 3.06±0.580.19, p<0.001), LFF (0.65±0.34 % vs. 0.14±0.09 %, p<0.001), AC (3.43±1.52 % vs. 1.67±0.67 %, p<0.001) and MD (3.40±2.73 µm2 vs. 1.09±0.720.23 µm2, p<0.001). ASA treatment mitigated the CIH-induced alterations in IMT: 44.07±2.73 µm; ED: 10.57±12.89 %; EF: 4.63±0.88; LFF: 0.25±0.17 % and AC: 0.90±0.13 % (p<0.01 for all comparisons). Conclusions: ASA prevents the CIH-induced aortic vascular remodeling, and should therefore be prospectively evaluated as adjuvant treatment in patients with OSA.